(NiZBRANNYE SO^INENIQ W DWUH TOMAH (B/s (N~ASTX (B2s - (NgOGOLX(B, (NnIKOLAJ wASILXEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1978)
(NwO WTOROJ TOM (B"(NiZBRANNYH SO^INENIJ(B" (Nn(B. (Nw(B. (NgOGOLQ WO[LI TAKIE [EDEWRY DRAMATURGII(B, (NKAK (B"(NrEWIZOR(B" (NI (B"(NvENITXBA(B", (NA TAKVE PO\MA (B"(NmERTWYE DU[I(B" - (NWER[INA TWOR^ESTWA PISATELQ(B, - (NOTRAZIW[AQ WSE MNOGOOBRAZIE RUSSKOJ VIZNI NA^ALA PRO[LOGO WEKA(B.s
rus
Keywords: (NsATIRA(B, (N@MORs; (NrUSSKAQ LITERATURAs